2021
DOI: 10.4236/ojas.2021.113026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Season and Lactation Number on Milk Production of Holstein Friesian Cows in Kabul Bini-Hesar Dairy Farm

Abstract: The present study was designed to investigate the effects of season and lactation number on milk yields in Holstein dairy cows at Kabul Bini Hesar Dairy Farm. For this purpose, data were collected from the dairy farm herd book records during 1392-1393 (2013-2014). Considering the milk yield stages of the cows, the total milk production was highest during the spring season 18,454.95 ± 33 L followed by summer 17,060.85 ± 34.5 L while the lowest milk production obtained in winter 16,398.45 ± 31.5 L. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The current study result was higher and contradictory to 223.68 ± 3.55 L and 229.32 ± 1.58 L in the wet and dry seasons of the year without a significance difference [ 56 ]. Habibi et al [ 57 ] reported a higher LMY of a Holstein Friesian cow of 17,060.85 ± 34.5 L in summer and 16,398.45 ± 31.5 L in winter as a friendly concept. Contrary to the current result, Darfour-Oduro et al [ 58 ] reported non-significant effects of season on LL for Sanga-Holstein Friesian crosses in Ghana with dissimilar results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study result was higher and contradictory to 223.68 ± 3.55 L and 229.32 ± 1.58 L in the wet and dry seasons of the year without a significance difference [ 56 ]. Habibi et al [ 57 ] reported a higher LMY of a Holstein Friesian cow of 17,060.85 ± 34.5 L in summer and 16,398.45 ± 31.5 L in winter as a friendly concept. Contrary to the current result, Darfour-Oduro et al [ 58 ] reported non-significant effects of season on LL for Sanga-Holstein Friesian crosses in Ghana with dissimilar results.…”
Section: Resultsmentioning
confidence: 99%
“…Demeke [ 38 ] reported the effects of lactation on DMY antagonistically. He testified that lactation phase increased, yield would decrease by 1.75 ± 0.12 L, 1.23 ± 0.10 L, and 0.98 ± 0.09 L. The direct proportionality of DMY and lactation stage was determined (12.04 ± 0.7, 13.24 ± 0.8, 14.10 ± 0.6 L) by Habibi et al [ 57 ]. The effects of lactation stage on yield were due to compensatory restoration of exhausted energy during gestation and parturition at the early stage and period of the preparation for the conceived fetus at late stage.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, cows having longer DO yielded milk more than those with shorter and moderate calving-conception intervals. The ORs for all categories of DO were less than one; hence, these values were inverted to denote more interpretable conclusions (El-Awady et al 2021 ; Habibi et al 2021 ). This means, compared to DO < 100 days, the probability that a cow will yield milk of more than 4500 kg will be 2.31 (1/0.432) times greater for those of DO > 400 days.…”
Section: Resultsmentioning
confidence: 99%